The Short-Term and Localized Effect of Gun Shows: Evidence from California and Texas - Duggan, Mark; Hjalmarsson, Randi; Jacob, Brian A. (The Review of Economics and Statistics, 2011)
Abstract We examine the effect of more than 3,400 gun shows using data from Gun and Knife Show Calendar and vital statistics data from California and Texas. Considering the one month following each show and a surrounding area ranging from 80 to 2,000 square miles, we find no evidence that gun shows increase either gun homicides or suicides. The similarity of our estimates for California and Texas suggests that the much tighter California gun show regulations do not substantially reduce the number of firearms-related deaths in that state. Using incident-level crime data for Houston, Texas, we also find no evidence of an effect on other crime categories.